Manipulation of Surface Potential Distribution Enhances Osteogenesis by Promoting Pro‐Angiogenic Macrophage Polarization via Activation of the PI3K‐Akt Signaling Pathway - Qun Cui; Xiaona Zheng; Yunyang Bai; Yaru Guo; Shuo Liu; Yanhui Lu; Lulu Liu; Jia Song; Yang Liu; Boon Chin Heng; Fuping You; Mingming Xu; et al. (Advanced Science)
Abstract Regulation of the immune response is key to promoting bone regeneration by electroactive biomaterials. However, how electrical signals at the micro‐ and nanoscale regulate the immune response and subsequent angiogenesis during bone regeneration remains to be elucidated. Here, the distinctly different surface potential distributions on charged poly(vinylidene fluoridetrifluoroethylene) (P(VDF‐TrFE)) matrix surfaces are established by altering the dimensions of ferroelectric nanofillers from 0D BaTiO3 nanoparticles (homogeneous surface potential distribution, HOPD) to 1D BaTiO3 nanofibers (heterogeneous surface potential distribution, HEPD). Compared to HOPD, HEPD is significantly better at inducing the M2 polarization of macrophages and promoting neovascularization, which results in accelerated bone regeneration in vivo. The transcriptomic analysis reveals that macrophages modulated by HEPD display high expression levels of pro‐angiogenic genes, which is corroborated by tube‐formation assays, RT‐qPCR, and western blot analyses in vitro. Mechanistic explorations elucidate activation of the PI3K‐Akt signaling pathway, which in turn induces the polarization of macrophages toward a pro‐angiogenic phenotype. This study elucidates the cascade of biological processes by which heterogeneous electrical signals at the micro‐ and nanoscale modulate macrophage functions to promote vascularization and bone regeneration. Hence, this study provides new insights into how the micro‐ and nanoscale distribution characteristics of electrical signals facilitate bone regeneration.